PS-R07-8: A CASE OF PRIMARY ALDOSTERONISM CAUSED BY BILATERAL ALDOSTERONE-PRODUCING MICROTUMORS WITH A UNILATERAL ADRENAL MASS. (January 2023) - Mizumoto, Teruhiko; Kakizoe, Yutaka; Date, Ryosuke; Itai, Yohei; Izumi, Yuichiro; Adachi, Masataka; Kuwabara, Takashige; Mukotyama, Masashi
Abstract : Introduction: Primary aldosteronism (PA) is defined as a disease in which overproduction of aldosterone causes various complications such as hypertension, cardiovascular disorder and kidney disease. We herein report a case of PA caused by bilateral aldosterone-producing microtumors with a unilateral adrenal mass. Case presentation: A 54-year-old man was referred to our hospital with a clinical suspicion of PA. He had a history of hypertension and chronic kidney disease for 10 years and had experienced paresthesia that was caused by putaminal hemorrhage in the past. In the initial examination, he exhibited hypertension (150/90 mmHg), high aldosterone (pg/mL)-to-renin (ng/mL/h) ratio (1, 744), and overt hypokalemia (K, 2.9 mEq/L). The serum creatinine level was 1.89 mg/dL. The captopril challenge test showed no changes in his blood pressure or plasma aldosterone concentration. These results led to a clinical diagnosis of PA. Computed tomography (CT) revealed the presence of left adrenal mass, so that we suspected that the mass should be responsible for overproduction of aldosterone. We performed adrenal venous sampling. Unexpectedly, the adrenal venous sampling highly suggested the presence of aldosterone-producing microtumors in bilateral adrenal glands (lateralized ratio, 1.3; left contralateral ratio, 0.2). After evaluation, we decided that there was no indication for the removal of left adrenal mass. Then, a low dose of a mineralocorticoid receptor (MR) antagonist was started. Although the dose of an MR antagonist could not be increased sufficiently due to poor renal function, he exhibited an improved control of blood pressure and was followed up thereafter. Discussion and Conclusion: Although PA is one of the most common causes of secondary hypertension, making an accurate diagnosis and appropriate treatment is sometimes problematic due to the difficulty in assessing the site of aldosterone overproduction. The Japanese Endocrine Society clinical guideline states that PA with unilateral adrenal tumor in young patients may not require adrenal venous sampling. From the current case, however, we should always consider the possibility of bilateral microtumors or hyperplasia even in the presence of a unilateral adrenal mass.